Identifikasi Hambatan Pada Bangunan Gedung Kampus Dalam Ketercapaian Kebijakan Sustainable Development Goals - Prafitasiwi, Avisha Gita; Rohman, Mohammad Arif; Alfianidah, Rizki (Universitas Jember, 2023)
The Green Building concept is one of the solutions to creating development while still paying attention to environmental aspects. Although the concept of green building offers a positive impact on the environment, the goal of an energy-saving system will not be optimally achieved if building occupants are not actively involved in the energy-saving process. ITS has made efforts to save energy through the Eco Campus program by involving building users. ITS building users already have a good awareness of energy savings, but several variables have substandard values. It is because the actions of building users to save energy will always be influenced by obstacles, considering the many parties involved in the process. This study analyzes the obstacles faced by building users in efforts to save electrical energy in ITS campus buildings. A total of 181 questionnaires were distributed to building users consisting of lecturers, staff, and students. The results of the study found that the most influential obstacles in efforts to save electrical energy were the lack of commitment to achieving success in electrical energy efficiency, electricity-saving policies that varied at each level of the bureaucracy, and the absence of binding regulations or policies. This research adds novelty to knowledge in the field of sustainable development, particularly in the analysis of barriers to achieving energy savings in campus buildings.Keywords: obstacles, green building, energy efficiency ABSTRAK Konsep Green Building merupakan satu dari banyak jalan keluar dalam menciptakan pembangunan dengan tetap memperhatikan aspek lingkungan. Meski konsep green building menawarkan dampak positif terhadap lingkungan, tujuan suatu sistem penghematan energi tidak akan tercapai secara maksimal jika pengguna gedung tidak secara aktif terlibat dalam proses penghematan energi. ITS memiliki upaya pencapaian penghematan energi melalui program Eco Campus dengan melibatkan pengguna gedungnya. Pengguna Gedung ITS telah memiliki kesadaran akan pentingnya penghematan energi yang baik, namun terdapat beberapa variabel yang memiliki nilai di bawah standar. Hal ini disebabkan aksi pengguna gedung untuk menghemat energi tidak akan lepas dari hambatan mengingat banyaknya pihak yang terlibat dalam proses tersebut. Penelitian ini menganalisis hambatan-hambatan yang dihadapi oleh pengguna gedung dalam upaya penghematan energi listrik di bangunan gedung kampus ITS. Sebanyak 181 kuesioner didistribusikan kepada pengguna gedung yang terdiri dari dosen, staff dan mahasiswa. Penelitian ini menunjukkan hambatan yang paling berpengaruh dalam upaya penghematan energi listrik adalah kurangnya komitmen untuk mencapai sukses dalam efisiensi energi listrik, kebijakan penghematan energi listrik yang berbeda-beda di setiap level birokrasi kampus, dan tidak adanya peraturan atau kebijakan yang mengikat. Penelitian ini menambahkan kebaruan ilmu pada bidang pembangunan berkelanjutan, khususnya dalam analisis hambatan dalam ketercapaian penghematan energi pada gedung kampus.Kata kunci: Hambatan, green building, efisiensi energi, Delphi